Clinical and immunological assessment of 94 patients with primary humoral immunodeficiency: Common variable immunodeficiency, selective IgA deficiency and polysaccharide antibody deficiency syndrome - Bezrodnik, Liliana (2011)
We present the clinical and B cell immunophenotypical characterization of 94 patients with Common Variable immunodeficiency (CVID), selective IgA deficiency (SIgAD) and polysaccharide antibody deficiency syndrome (SAD). Study design: We retrospectively investigated clinical findings and B cell compartment in 31 patients with CVID, 35 with SIgAD and 28 with SAD. Regardless of underlying disease, a delay was observed between age at diagnosis and onset of first symptoms. The predominant clinical findings were upper and lower respiratory tract infections. Allergic symptoms were more frequent in SAD and SIgAD patients, hematological and autoimmune manifestations in CVID and celiac disease in SIgAD. B-cell Immunophenotype abnormalities were observed in SAD and CVID patients: both had reduced memory B cells (CD19{+} CD27{+}), and increased transitional B cells (CD24{ + + } CD38{+ +}) was found in SAD. We did not find any statistically significant abnormalities in any of differentiation stages of B cells in SIgAD. Defects of the B cell compartment were associated with bronchiectasis, splenomegaly, autoimmunity and/or malignancy in CVID and SAD patients.We conclude that flow cytometric evaluation of the B cell compartment could be a useful tool for the diagnosis and follow up of these patients.